The Aegina of Gleb Bogomolov: Painting as an Artifact - Staniukovich-Denisova, Ekaterina Iu.; Baryshnikova, Elizaveta V. (Actual Problems of Theory and History of Art, 2017)
In 2016 the International Conference “Actual Problems of Theory and History of Art VII” withthe discussion focusing on “Artifact, Art-object, Argument. An object in Visual Arts: Tasks, Methods, Results” chose as its emblem the painting “Aegina” by the St. Petersburg artist Gleb Bogomolov. This large-scale paintingbecomes the starting point for analyzing the final period of the master’s work in the context of the classical tradition in contemporary art interpretation. Bogomolov’s multi-channeled creativity allowed choosing his work as an emblem, in which, as in cultural code, one can read many meanings, associated with the problems of contemporary art history and museology discussed at the conference.
Keywords: Gleb Bogomolov; Russian painting; artifact; Aegina; emblem; actual problems of theory and history of art